A Description of The Psychological Well-Being of Parents Who Have Children With Special Needs at Slb Asuhan Kasih Kupang - Ludji, Maleakhi; Damayanti, Yeni; Mage, Mernon Yerlinda Carlista (Universitas Nusa Cendana, 2024)
This study explores the psychological well-being of parents with children who have special needs and physical disabilities at the Asuhan Kasih Kupang special school. Six participants, selected through purposive sampling, were involved based on predefined criteria. Using qualitative methods, data was collected through interviews and analyzed using thematic analysis, revealing three key themes: acceptance, caregiving, and social support. The findings indicate that parents' psychological well-being is shaped by their ability to accept their child's condition, develop effective parenting strategies—such as fostering independence and offering positive affirmations—and rely on social support, including emotional, practical, and moral assistance. The study highlights the importance of coping strategies, such as engaging in spiritual activities to enhance gratitude, spending quality time with children, and fostering communication between schools and parents to alleviate anxiety. These insights provide valuable recommendations for enhancing parental well-being and caregiving practices.